Manusia Dalam Bumi Manusia Pramoedya Ananta Toer - Nur Cholis; Diah Dwi Ikra Negara; M. Samsul Ma’arif (Manthiq, 2023)
Abstract, Human earth is a contro.versial and interesting novel, Pramo.edya Ananta Toer as the wri.ter is acc.used of being involved with the comm.unists. Earth of Mankind was banned from circulating, but then it got a crowded place among readers and has been translated into more or less 36 languages, the ideas and messages will eventually give color to the reader com.munity, how to think, behave and exist. This study is a discourse ana.lysis model that aims to describe human exist.ence in the Earth of human using hermeneutic objective method as an analytical approach. The final result can be concluded that the humans who exist in this Earth of human are none other than those who are armed with knowl.edge and freedom who are able to struggle out of the various difficulties they face, are able to stand on their own feet, and do not become crimi.nals running away from respon.sibility. The concept of humanity in Bumi Manusia is rooted in the factual social conditions of the poor and the oppressed. Humans who exist on earth. Humans do not portray perfect humans, or ideal humans who are aspired to, succeed in winning with achievements based on perfect human ideals filled with perfection, but humans who are able to continue to struggle to get out of the factual tests experienced humans on earth. Because, according to Pramoedya, the perfect, successful and always victorious human does not exist on earth but in heaven. Keywords; Human Earth, Existence, Human  Abstrak, Bu.mi Manu.sia meru.pakan no.vel kontr.oversial dan menarik, Pramo.edya Ananta Toer sebagai penulis dituduh terlibat dengan komunis. Bumi Manusia sempat dilarang beredar tetapi kemudian mendapatkan tempat  ramai dikala.ngan pembaca dan sudah diterje.mahkan kurang lebih dalam 36 bahasa, gagasan dan pesannya pada akhirnya akan ikut memberikan warna terhadap masyarakat pembaca, bagaimana berfikir, bersikap dan bereksistensi. Kajian ini adalah model analisis wacana yang bertujuan mendeskripsikan eksistensi manu.sia dalam Bumi Manusia dengan metode objektif hermeneutic sebagai pendekatan analisis. Hasil akhir dapat disimpulkan bahwa manusia yang eksis dalam Bumi Manusia tidak lain adalah mereka yang berbekal pengetahuan dan kemerdekaan mampu berjuang keluar dari berbagai kesulitan yang dihadapi, mampu berdiri pada kaki sendiri, dan tidak menjadi kriminal lari dari tanggung jawab. Konsep kemanu.siaan dalam Bumi Manusia mengakar pada kondisi faktual sosial rakyat kecil dan kaum tertindas. Manusia yang eksis dalam bumi Manusia tidak mencitrakan manusia semp.urna, atau manusia ideal yang dicita-citakan, sukses menang dengan pencapaian yang didasarkan pada cita-cita manusia paripurna yang diliputi kesem.purnaan, melainkan manusia yang mampu terus berjuang untuk keluar dari ujian-ujian faktual yang dialami manusia di bumi. Karena manusia yang sempurna, sukses dan senantiasa menjadi pemenang menurut Pramoedyatidak ada di bumi melainkan ada di surga. Kata Kunci; Bumi Manusia, Eksistensi, Manusia